JUSTIFICATION OF THE FEASIBILITY OF PRODUCING MINCED QUAIL MEAT - Самілик, Марина (SWorldJournal, 2025)
The object of this study is the process of assessing the safety of agricultural products in the area near military operations. It is known that military operations lead to contamination of the ecosystem with heavy metals. However, it has not been studied